ANALISIS RENCANA PELAKSANAAN PEMBELARAN TEMATIK SECARA DARING SELAMA MASA PANDEMI COVID-19 - Rexsi Seles; Siti Halidjah; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract This study aims to describe the preparation of an online thematic learning implementation plan by teacher of elementary school 15 South Pontianak during the Covid-19 pandemic. This study use the descriptive qualitative research methods. The data source of this research is the fifth grade teacher of elementary school 15 South Pontianak and the data is the online thematic learning implementation plan document 1 st to 3rd learning meetings. The results of the analysis show the components of the learning implementation plan made by the teacher are guided by the Circular of the Ministry of Education and Culture Number 14 of 2019 Contain the core components, namely learning objectives, learning activities and evaluations. There are 14 learning objectives that meet the criteria according to basic competencies but are still not in accordance with the A.B.C.D method. Learning activities only in learning 1 and 2 meet the criteria in accordance with the learning objectives while in learning 3 there are 12 steps of activity that do not meet the criteria according to the knowledge and skills aspects, while the psychomotor aspect has not met the appropriate criteria. Keywords: analysis, online learning implementations plan, covid-19